The Assessment of Awareness and Practices About Menstrual Hygiene Among College Students - Arif, Lubna; Akram, Muquddus; Baqir, Lubna; Bashir, Asma; Ishfaq, Shabana; Anwar, Ghuzala; Yasin, Iqra (Biological and Clinical Sciences Research Journal, 2026)
Menstrual hygiene management is an important component of women’s reproductive health. In many developing countries, including Pakistan, cultural taboos, limited education, and inadequate institutional facilities may influence awareness and hygienic practices among young females. Objective: To assess the level of awareness and practices regarding menstrual hygiene among college students. Methods: A descriptive cross-sectional study was conducted at KIPS College, Kasur, Pakistan, from January 2025 to June 2025. A total of 171 female intermediate-level students were recruited using convenience sampling. Data were collected using a structured questionnaire that included demographic characteristics, menstrual hygiene awareness, and menstrual hygiene practices. Awareness was measured using a 15-item Likert scale, while practices were evaluated through 12 practice-related items. Data were analysed using SPSS, and descriptive statistics, including frequencies, percentages, means, and standard deviations, were calculated. Results: Among 171 participants, most students were aged 15–17 years (92.4%). Overall, 55.6% of students demonstrated moderate awareness of menstrual hygiene, while 21.6% showed high awareness. Most participants were aware of menstrual products (74.2%) and the importance of regularly changing them (92.4%). Regarding hygiene practices, 87.1% reported always using hygienic absorbents, and 86.5% used water and soap for genital cleaning during menstruation. However, only 16.4% reported taking a daily bath during menstruation, and only 39.8% indicated that their college consistently provided adequate menstrual hygiene facilities. Conclusion: The study indicates that college students possess moderate awareness and generally satisfactory menstrual hygiene practices; however, gaps remain in certain hygienic behaviors and institutional support. Strengthening menstrual health education and improving sanitation facilities in educational institutions may further enhance safe menstrual hygiene practices among young females.